2022
DOI: 10.1002/mc.23486
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin synergistically enhances the cytotoxic effects of oxaliplatin in colon cancer by targeting the PHB2‐RCHY1 mediated signaling pathway

Abstract: Dihydroartemisinin (DHA) has recently attracted increasing attention for its low toxicity and high antitumor activity. DHA has been reported to have synergistic anticancer effects with a variety of drugs in the clinic; however, the molecular mechanism by which DHA inhibits tumorigenesis and improves oxaliplatin cytotoxicity in colon cancer cells is still not well understood. In this study, we found that DHA can inhibit cell proliferation and colony formation in a dose-dependent manner. Prohibitin 2 (PHB2) is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…Overexpression of PHB2 enhances colon cancer growth in vitro and in vivo. PHB2 was reported as a novel target of Dihydroartemisinin (DHA) in colon cancer [ 49 ]. DHA is an effective clinical drug for treatment of malaria, but it also has promising anticancer effects that have been tested in many cancers [ 66 ].…”
Section: Phb2 Oncogenic Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression of PHB2 enhances colon cancer growth in vitro and in vivo. PHB2 was reported as a novel target of Dihydroartemisinin (DHA) in colon cancer [ 49 ]. DHA is an effective clinical drug for treatment of malaria, but it also has promising anticancer effects that have been tested in many cancers [ 66 ].…”
Section: Phb2 Oncogenic Functionmentioning
confidence: 99%
“…The proposed mechanism is through DHA inhibiting the expression of PHB2 in a ubiquitylation-dependent manner and reversing PHB2-induced RCHY1 (RING finger and CHY zinc finger domain-containing protein 1) expression, as well as suppressing p53 and p21 expression. Therefore, both PHB2 and RCHY1 are promising targets in colon cancer therapy [ 49 ].…”
Section: Phb2 Oncogenic Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell proliferation activity was determined using the CCK8 assay according to a protocol described in a previous study [20]. In brief, 100 µL of cell suspension was plated into 96-well plates (5×10 3 /well for RKO cells, 8×10 3 /well for HCT116 cells) and incubated overnight.…”
Section: Cell Culture and Cell Assaysmentioning
confidence: 99%
“…DHA exerts its antitumour activity via various mechanisms, such as inhibiting proliferation, metastasis and angiogenesis and promoting apoptosis and immune function [2].Previous studies by our group and other groups reported that DHA can enhance the antitumour activity of a variety of chemotherapeutic drugs [3][4][5]. In our previous study, we found that DHA can enhance the cytotoxic effects of oxaliplatin in colon cancer [3]. However, the molecular mechanism by which DHA enhances antitumour activity is incompletely understood.…”
Section: Introductionmentioning
confidence: 98%